CO2-assisted compression-adsorption hybrid for cooling and desalination - Ali, Syed Muztuza (2017)
This paper presents a novel compression-adsorption hybrid that symbiotically combines adsorption and CO2 compression cooling devices. The seemingly low efficiency of each cycle individually is overcome by an amalgamation with the other. Hence, both heat and water vapour refrigerant mass are recovered for continuous cooling and desalination. Two different configurations are presented. The first configuration deals with a two-stage heat recovery system. At the first stage, heat is recovered from the compressed carbon dioxide to drive the adsorption device. The second stage heat recovery system internally exchanges heat between the low pressure and high pressure refrigerants of the CO2 cycle. The second configuration is proposed with an additional third-stage heat recovery from the gas cooler to the high pressure evaporator of the adsorption cycle. The water vapour mass is recovered from bed-to-bed adsorption at relatively higher pressure. A detailed thermodynamic framework is presented to simulate the performances in terms of COP (coefficient of performance), SCP (specific cooling power), SDWP (specific daily water production), PR (performance ratio) and OCR (overall conversion ratio). It is found that the overall COP is improved by more than 60% as compared to the conventional CO2 cycle, and in addition, the system generates 12.7 m3 of desalinated water per tonne of silica gel per day as extra benefits. Furthermore, both the heat and mass recoveries improve the overall conversion ratio, which is almost double as compared to the conventional CO2 cycle.